Translatabilitas Phrasal Verbs ke dalam Bahasa Indonesia - Tapilatu, Terweline; Lewaherilla, August (DINAMIS, 2023)
This qualitative study focuses on the translatability of phrasal verbs by exploring the problem of their untranslatability into Indonesian, strategies for overcoming this issue and achieving meaning equivalence between the source and the target texts. The issue of untranslatability of phrasal verbs can arise due to the lack of equivalents with the same meaning as the source text, target language equivalents that are too formal and not commonly used in informal conversations, the absence of specific equivalents for the phrasal verbs, target language equivalents that are too lengthy and may result in inefficient sentences, and the phrasal verb’s meaning being too specific for its equivalents to be used in all contexts. This problem of untranslatability can be addressed by implementing strategies such as paraphrasing, offering additional information to complete the target text meaning, and applying modulation. Equivalence between the two texts is attained by using equivalents that can function in the same situation as the source text, providing equivalents in the form of explanations or additional information, using equivalents that explain the meaning from a different perspective. Additionally, equivalents have to be determined based on context in which the phrasal verbs are used, and the selection of equivalents should not be limited to the verb category only. Although there are no phrasal verbs in Indonesian, they can still be translated because the transfer is of the meaning rather than the language form. When both texts are equivalent, it suggests that the translator has a strong grasp of the source and target languages and has made appropriate adjustments to convey the intended meaning. This study aims to enhance the field of translation studies, specifically in regards to the translatability of phrasal verbs.